The Phenomenon of Pre-Marriage Pregnancy Among Adolescents: An Analysis Regarding the Causes and Solutions - Aisyah Cantika; Aulia Syahrinanda; Melinda Pridayani; Hadissa Zuriati; Nurfiza Angsisca; Zulvia Ekawati (International Journal of Multidisciplinary Research of Higher Education, 2018)
Adolescence is vulnerable to deviant behaviour, therefore the role of the family, especially parents, is needed in supervising their children, especially teenagers. Reports from previous researchers found a high rate of teenage pregnancies before marriage and these rates have always shown an increase until now. Precisely that this research is to analyse what are the factors that cause teenage pregnancies before marriage and as solutions to prevent them. This study uses a qualitative method with a phenomenological approach. Sources of data were taken from six informants by direct interviews. All data were then analysed using the Miles and Huberman technique. The research findings show three factors causing this behaviour to occur; i) low parental supervision, ii) falling into promiscuity, iii) lack of understanding of religion. Furthermore, three ways of prevention are i) the need for parental supervision, ii) the collaboration of all parties in the community and iii) instilling religious knowledge in adolescents.